HISTOLOGICAL FINDINGS OF THE BURSA OF FABRICIUS IN BROILER CHICKS SUPPLIED WITH THE METHIONINE SUPPLEMENT METHIO GROW - Ali Hassan et al.,... (Basrah Journal of Veterinary Research)
The study aimed to determine the effects of higher levels of methioninesupplementation than the recommended NRC level in the diets on the weight andhistomorphology of the bursa of Fabricius as indicators for the immune status of broilerchickens. A total of 60, one-day-old, broiler chicks were divided into 4 groups (Control, T1,T2, and T3 groups) and accommodated in separate pens at the College of AgriculturalEngineering Sciences, University of Sulaimani. The chicks were fed on a starter diet for thefirst 11, a grower diet on days 12-25 and a finisher diet on days 26-42. The methioninesupplement MethioGrow was added daily to the drinking water of the treatment groups T1, T2, and T3 by the levels 0.25, 0.50, 0.75 ml per liter respectively for 42 days, whereas thoseof the control group were provided with additives-free drinking water. On day 42, the chickswere euthanized and the bursa of Fabricius was excised, weighed by a sensitive balance and5μm thick tissue sections were obtained, stained by Hematoxylin and Eosin stains andexamined by a light microscope to examine the histological findings. The weights’ mean ofthe bursa of Fabricius on day 42 was significantly higher in groups T2 and T3 than in thecontrol group and the microscopic examination of the bursa of Fabricius revealed slightincrease in numbers of lymphocytes in the medullary region of the lymphoid follicles inchicks of the treatment groups 1 and 2 (T1 and T2) and slight increase in lymphocytes inboth the cortical and medullary regions of the lymphoid follicles in chicks of the treatmentgroup 3 (T3) in comparison with chicks of the control group. In conclusion, the obtainedresults revealed that supplementation of higher levels of methionine in the broiler diet thanthe level recommended by the NRC has positive effects on the immune status of the broilersand they support the suggestions of previous reports that referred to the insufficiency ofmethionine requirements of broiler based on recommendations of NRC to meet the realrequirements of the commercial poultry farms.